The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019 Ninth International Conference on Image Processing Theory, Tools and Applications (IPTA) 2019
DOI: 10.1109/ipta.2019.8936114
|View full text |Cite
|
Sign up to set email alerts
|

MicroExpNet: An Extremely Small and Fast Model For Expression Recognition From Face Images

Abstract: This paper is aimed at creating extremely small and fast convolutional neural networks (CNN) for the problem of facial expression recognition (FER) from frontal face images. To this end, we employed the popular knowledge distillation (KD) method and identified two major shortcomings with its use: 1) a fine-grained grid search is needed for tuning the temperature hyperparameter and 2) to find the optimal size-accuracy balance, one needs to search for the final network size (i.e. the compression rate). On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
(84 reference statements)
0
20
0
Order By: Relevance
“…Facial Expression. The proposed system uses MicroExpNet [14] to extract the facial expressions of the coachees. This is a small and fast convolutional neural network designed for facial expression recognition, which is obtained by distilling a heavy and accurate neural network.…”
Section: Multimodal Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial Expression. The proposed system uses MicroExpNet [14] to extract the facial expressions of the coachees. This is a small and fast convolutional neural network designed for facial expression recognition, which is obtained by distilling a heavy and accurate neural network.…”
Section: Multimodal Inputmentioning
confidence: 99%
“…This is a small and fast convolutional neural network designed for facial expression recognition, which is obtained by distilling a heavy and accurate neural network. Çugu et al [14] reported that the network achieved over 95.0% classification accuracy for the eight expressions of "neutral, " "anger, " "contempt, " "disgust, " "fear, " "happy, " "sadness, " and "surprise" under the real-time conditions. Therefore, we decided to use this network to meet requirement (2).…”
Section: Multimodal Inputmentioning
confidence: 99%
“…Our SD-CNN method is compared with the recent state-of-the-art FER methods, including DeRL [ 12 ], FN2EN [ 18 ], FMPN [ 28 ], VGG-face [ 8 ], MicroExpNet [ 34 ], GoogLeNet [ 17 ], MultiAttention [ 24 ], DSAE [ 26 ], GCNet [ 40 ], DynamicMTL [ 41 ], IA-gen [ 20 ], CompactCNN [ 30 ], DTAGN(Joint) [ 29 ], CPPN [ 27 ], DPND [ 10 ], PPDN [ 11 ], and FAN [ 31 ]. Table 2 reports our experimental results and shows the comparisons with these methods.…”
Section: Resultsmentioning
confidence: 99%
“…Our SD-CNN is also compared with the recent state-of-the-art methods, including FN2EN [ 18 ], DeRL [ 12 ], GoogLeNet (fine-tuned) [ 17 ], VGG-face (fine-tuned) [ 8 ], GCNet [ 40 ], DynamicMTL [ 41 ], MicroExpNet [ 34 ], MultiAttention [ 24 ], IA-gen [ 20 ], PPDN [ 11 ], DPND [ 10 ], DTAGN(Joint) [ 29 ], and CompactCNN [ 30 ], on the Oulu-CASIA dataset. As shown in Table 3 , our method achieves the highest accuracy of 91.3 %, which outperforms the state-of-the-art static image-based method (i.e., the DynamicMTL [ 41 ]) by 1.7% and also suppresses the state-of-the-art sequence-based method (i.e., the CompactCNN [ 30 ]) by 2.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation